Predicted polymorph manipulation in an exotic double perovskite oxide. Issue 39 (30th September 2019) - Su, He-Ping; Li, Shu-Fang; Han, Yifeng; Wu, Mei-Xia; Gui, Churen; Chang, Yanfen; Croft, Mark; Ehrlich, Steven; Khalid, Syed; Adem, Umut; Dong, Shuai; Sun, Young; et al.
Abstract : First-principles density functional theory calculations, for the first time, was used to predict the Mg3 TeO6 -to-perovskite type phase transition in Mn3 TeO6 at around 5 GPa. Abstract : Predicted polymorph manipulation offers a cutting-edge route to design function-oriented materials in an exotic double perovskite-related oxide A2 BB′O6 with small A-site cations. Herein, first-principles density functional theory calculations in light of the equation of state for solid, for the first time, was used to predict the Mg3 TeO6 ( R 3̄)-to-perovskite ( P 21 / n ) type phase transition in Mn3 TeO6 at around 5 GPa, regardless of the deployment of magnetic interactions. The high-pressure synthesis and synchrotron diffraction crystal structure analysis corroborated experimentally the polymorph variation in Mn2 2+ Mn 2+ Te 6+ O6, which was accompanied by a 13 K increase in the antiferromagnetic ordering temperature (37 K) in the high-pressure perovskite polymorph compared to that of the ambient-pressure R 3̄ phase (24 K). The magnetodielectric coupling remains up to 50 K with the maximum being around the magnetic ordering temperature in the perovskite Mn3 TeO6 . Thus, the predicted polymorph manipulation here offers the possibility of discovering accelerated materials by inverse design in exotic perovskite oxides.